La réception du modèle graphique de Burgess dans la géographie française des années cinquante aux années soixante-dix - Pascal Clerc; Jacquemine Garel (Cybergeo, 1998)
It is common practice nowadays to use the Burgess graphic model to explain intra-urban city's structures. It was built up in the twenties and French geographers came to know about it before the thirties. Its diffusion among the scientific community is due to papers from the French sociologist Maurice Halbwachs and the American geographers Harris and Ullman. We are drawing here a sample of the ways this model was received in French geography. Our intentions remain modest: to throw light on an interesting and unknown research material, to draw up a research question. We analyze the welcoming of the Burgess model as a product of a confrontation between two analysis grids of urban space, both associated with two different epistemological corpus : French geographers have translated, according to their conceptual background, the researches of this American sociologist, which remained peculiar to them in many ways. Studying the graphic transformations in the concentric model allows to underline this process of intellectual embezzlement.